A new Cernosvitoviella species (Clitellata: Enchytraeidae) and its comparison with other Cernosvitoviella species from Sphagnum mires in Hungary - Dózsa-Farkas, Klára; Csitári, Bianka; Felföldi, Tamás (Zootaxa, 2017)
Results of a comparative investigation on five Cernosvitoviella species from Hungarian Sphagnum mires including their distribution and the description of a new species, Cernosvitoviella farkasi sp. n., are presented in this paper. Cernosvitoviella atrata, C. aggtelekiensis, C. crassoductus and C. farkasi sp. n. could be easily distinguished from each other based on both morphological and molecular taxonomic analyses. However, C. minor seems to be a species complex on the basis of these investigations, so it was referred as C. minor sensu lato. The status of the C. minor variants requires further studies.